2020
DOI: 10.1080/23279095.2020.1807348
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric assessment of social cognitive tasks

Abstract: Although there has been a marked increase in interest in social cognition (SC) in recent years, psychometric data relating to many tasks used to measure its components remain limited in healthy populations with only five articles published to date. It is accordingly premature to speak of a consensus concerning the specific components, or best tests of the components, and possible cultural differences. The present study sought to partially fill that gap, examining the psychometric properties of a battery of SC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 110 publications
0
1
0
1
Order By: Relevance
“…The current study extends prior research that was focused on the psychometric qualities of SC measures of SC (Gourlay et al, 2020), with the primary objectives of 1) identifying age variations in SC abilities across the stages of adulthood and 2) clarifying the nature of the relations among SC components in a pathway through which they might relate to social relationships. To accomplish these research objectives, we opted to perform exploratory analyses in a first step, to identify potential factors that may affect the variables being studied (i.e., age and SC components).…”
Section: Objectivesmentioning
confidence: 83%
See 2 more Smart Citations
“…The current study extends prior research that was focused on the psychometric qualities of SC measures of SC (Gourlay et al, 2020), with the primary objectives of 1) identifying age variations in SC abilities across the stages of adulthood and 2) clarifying the nature of the relations among SC components in a pathway through which they might relate to social relationships. To accomplish these research objectives, we opted to perform exploratory analyses in a first step, to identify potential factors that may affect the variables being studied (i.e., age and SC components).…”
Section: Objectivesmentioning
confidence: 83%
“…The pertinent studies focused particularity on the relationship between emotion recognition and ToM abilities. For example, Gourlay et al (2020) reported associations between emotion recognition and ToM, while Halberstadt et al (2011) found in their study that emotion recognition fully mediates the relationship between age and ToM. Mitchell and Phillips (2015) found that lower-level perceptual processes, including emotion recognition, occur at an earlier temporal stage than the higher-level process that is ToM, which requires integration and inference of more complex social information.…”
Section: Relationships Between Each Component Of Social Cognitionmentioning
confidence: 96%
See 1 more Smart Citation
“…Despite this, French HAB assessments are currently few. We are only aware of French versions of the Ambiguous Intentions Hostility Questionnaire (AIHQ; Gourlay et al, 2022; original version: Combs et al, 2007) and the Social Information Processing–Attribution and Emotional Response Questionnaire (SIP-AEQ; Gagnon et al, 2015; original version: Coccaro et al, 2009). Although valuable, these instruments have relatively low content coverage of ambiguous situations, where HAB can be meaningfully measured.…”
mentioning
confidence: 99%
“…Si bien no existe consenso sobre los diferentes sub dominios que integran la Cognición Social (CS) (Gourlay et al, 2020), algunos de los que tienen en la actualidad mayor consenso son: (a) Teoría de la Mente (TdM), que hace referencia a la capacidad para inferir estados mentales de los otros (creencias, metas, pensamientos, intenciones, entre otros) y construir una teoría sobre ellos (Baron- Cohen et al, 1985;Brüne, 2005), (b) la empatía, considerada como la capacidad para ser sensibles y comprender los estados sentimentales y afectivos de otras personas, sin que estos sean comunicados de manera explícita. Este subdominio se relaciona con la disposición para actuar a partir de esta comprensión (Baron- Cohen, 2009), (c) la percepción social que se refiere a la capacidad para identificar y valorar reglas y roles sociales, (d) el conocimiento social, entendido como la capacidad para identificar y hacer juicios sobre los aspectos sociales particulares de diversas situaciones (Addington et al, 2006), (e) el procesamiento emocional, definido como la capacidad para identificar, denominar, comprender, expresar y manejar emociones primarias y sociales a través del lenguaje verbal y no verbal (Baron- Cohen, 2009), y (f) el estilo atribucional como la manera en que cada persona explica las causas y consecuencias sobre diferentes situaciones sociales (Green et al, 2005;Penn et al, 2005).…”
unclassified